Immunological Aspect of Radiation-Induced Pneumonitis, Current Treatment Strategies, and Future Prospects - Kainthola, Anup; Haritwal, Teena; Tiwari, Mrinialini; Gupta, Noopur; Parvez, Suhel; Tiwari, Manisha; Prakash, Hrideysh; Agrawala, Paban K. (Frontiers in Immunology, 2017)
Delivery of high doses of radiation to thoracic region, particularly with non-small cell lung cancer patients, becomes difficult due to subsequent complications arising in the lungs of the patient. Radiation induced pneumonitis is an early event evident in most radiation exposed patients observed within 2-4 months of treatment and leading to fibrosis later. Several cytokines and inflammatory molecules interplay in the vicinity of the tissue developing radiation injury leading to pneumonitis and fibrosis. While certain cytokines may be exploited as biomarkers, they also appear to be a potent target of intervention at transcriptional level. Initiation and progression of pnemonitis and fibrosis thus are dynamic processes arising after few months to year after irradiation of the lung tissue. Currently available treatment strategies are challenged by the major dose limiting complications that curtails success of the treatment as well as well being of the patient’s future life. Several approaches have been in practice while many other are still being explored to overcome such complications. The current review gives a brief account of the immunological aspects, existing management practices and suggests possible futuristic approaches.